Training in Creating Financial Reports and Tax Reporting for New Enterpreneurs At SMKS Ma’arif Jakarta - Firdayetti, Firdayetti; Wijaya, Aji Kusuma; Ratnawati, Nirkudita; Agustina, Rizka; Azzahroh, Aulia; Anggraini, Dewi (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Many young entrepreneurs, especially vocational high school students, still face difficulties in preparing financial reports that meet standards and understanding tax obligations. In fact, good financial reports and tax compliance are important factors in business sustainability. Therefore, training is needed that can equip them with basic skills in recording transactions, preparing financial reports, and tax reporting. This training aims to improve vocational high school students' understanding in making simple financial reports and reporting taxes independently in accordance with applicable regulations. The training is carried out with a qualitative approach through theoretical explanations, case studies, direct practice using accounting software, and evaluation of understanding through pre-tests and post-tests. In addition, interviews were conducted with business actors to provide real insights into the importance of financial reports and tax compliance in the business world. The results of the training showed an increase in students' understanding in preparing financial reports and filling out annual tax returns. However, there are still obstacles in the use of accounting technology and understanding several more complex tax concepts. This training provides significant benefits in improving the skills of SMKS Ma'Arif Jakarta students in financial management and tax compliance. In the future, further assistance and integration of technology in learning are needed to ensure that students can apply the knowledge they have acquired effectively in the business world.